Consensus guidelines for the diagnosis and management of invasive candidiasis in haematology, oncology and intensive care settings, 2021. (22nd December 2021) - Keighley, Caitlin; Cooley, Louise; Morris, Arthur J.; Ritchie, David; Clark, Julia E.; Boan, Peter; Worth, Leon J.; ,
Abstract: Patients with haematological malignancies, haemopoietic stem cell transplant recipients and patients requiring admission to intensive care settings are at high risk for invasive candidiasis (IC). Over the past decade, there has been increased reporting of non‐ albicans species and fluconazole resistance in Australia. These guidelines provide updated evidence‐based recommendations for the diagnosis and management of IC in adult and paediatric haematology, oncology and intensive care settings. Optimal pharmacological and non‐pharmacological management are discussed. Recent studies strengthen the recommendation for an echinocandin agent as first‐line therapy for high‐risk patients with IC. Mortality benefit has also been demonstrated for non‐pharmacological management, including removal of central venous catheters, infectious diseases consultation and use of care bundles. Healthcare facilities managing immunocompromised patient populations should therefore adopt implementation strategies for these multimodal interventions.